What Mn Kβ spectroscopy reveals concerning the oxidation states of the Mn cluster in photosystem II. Issue 40 (6th October 2017) - Petrie, Simon; Stranger, Rob; Pace, Ron J.
Abstract : Structure of the Mn Cluster in the Oxygen Evolving Centre of Photosystem II, from Spectroscopy and Computational Chemical Modelling. Abstract : The oxygen evolving complex, (OEC) in Photosystem II contains a Mn4 Ca cluster and catalyses oxidation of water to molecular oxygen and protons, the most energetically demanding reaction in nature. The catalytic mechanism remains unresolved and the precise Mn oxidation levels through which the cluster cycles during functional turnover are controversial. Two proposals for these redox levels exist; the 'high' and 'low' oxidation state paradigms, which differ systematically by two oxidation equivalents throughout the redox accumulating catalytic S state cycle (states S0 …S3 ). Presently the 'high' paradigm is more favored. For S1 the assumed mean redox levels of Mn are 3.5 (high) and 3.0 (low) respectively. Mn K region X-ray spectroscopy has been extensively used to examine the OEC Mn oxidation levels, with Kβ emission spectroscopy increasingly the method of choice. Here we review the results from application of this and closely related techniques to PS II, building on our earlier examination of these and other data on the OEC oxidation states (Pace et al., Dalton Trans., 2012, 41, 11145). We compare the most recent results with a range of earlier Mn Kβ experiments on the photosystem and related model Mn systems. New analyses of these data are given, highlighting certain key spectral considerations which appear not to have been sufficiently appreciated earlier. These show that the recent and earlier PS II Kβ results have a natural internal consistency, leading to the strong conclusion that the low paradigm oxidation state assignment for the functional OEC is favoured.